Sovereign reputation and yield spreads: A case study on retroactive legislation - Otto Randl; Josef Zechner (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
This paper uses recent legislation in Austria to establish a link between sovereign reputation and yield spreads. In 2009, Hypo Alpe Adria International, a bank previously co-owned by the regional government of Carinthia, had been nationalized by Austria's central government in order to avoid a default triggering multi-billion Euro local government guarantees. In 2015, special legislation retroactively introduced collective action clauses allowing a haircut on both the bonds and the guarantees while avoiding formal default. We document that legislative and administrative action designed to partly abrogate the guarantees resulted in a loss of reputation, leading to higher yield spreads for sovereign debt. Our analysis of covered bonds uncovers an increase in yield spreads on the secondary market and a deterioration of primary market conditions.
urn:nbn:de:hebis:30:3-416841
Keywords: 330